CSH/SBE-β-CD nanoparticles: controlled synthesis and application for loading and pH-responsive drug release. (27th June 2022) - Yi, Chunrong; Li, Ying; Zhang, Shuxin; Fan, Hai; Cheng, Ziqiang
Abstract : CSH and SBE-β-CD were assembled via electrostatic interaction and hydrogen bonding for the loading and pH-responsive release of BSA. Abstract : Due to their limited oral bioavailability, poultry protein drugs have been mostly delivered by injections in the past few decades, leading to the stress response. Therefore, researchers have turned to developing new drug delivery systems to improve the oral bioavailability of these drugs. In this paper, nanoparticles were prepared via ionic cross-linking between SBE-β-CD and CSH, and BSA was chosen as a model protein to investigate the loading capacity. Additionally, the targeted and controlled release of BSA in the intestinal tract was studied. SEM results show that uniform and stable nanoparticles were formed, and when the concentrations of both CSH and SBE-β-CD were 2.0 mg mL −1, the loading capacity of BSA could reach 88.89%, with a release rate of up to 85.0% at pH 7.4 for 48 h in vitro . In addition, the release rate was 85.4% at pH = 5.0 within 8 h, which indicated that the drug delivery system was suitable for the targeted release of anti-cancer drugs. In conclusion, nanoparticles could be formed by SBE-β-CD and CSH, and protein drugs could be loaded by this system effectively. Targeted and controlled release of protein drugs could be achieved in the intestinal tract and cancer cells, which can improve the stability of protein drugs and prolong the drug action time, thus improving the oral bioavailability of protein drugs.